P149 Patient involvement in sexual health service delivery. (8th June 2017) - Meyrick, Jane; Gray, Debra; Jones, Abigail
Abstract : Introduction: Sexual and reproductive health and HIV (SRHH) services face unique PPI challenges, as the anonymity and confidentiality required by service users can be a barrier to attracting patient input. PPI could improve sexual health services, through increased trust in services and the ability to tackle sexual health inequalities. However, specific practical guidance on how to address PPI in sexual health and the evidence to support it is sparse. Methods: This research aimed to begin building an evidence base for PPI in sexual health services through: 1) an audit of PPI in SRHH in the Bristol region; and 2) a parallel survey of potential users of sexual health services about their experiences of PPI. For the audit, 18 SRHH organisations from all those in the region invited complete a short online survey, representing a range of different service providers. For the online survey, 96 sexually active young people were recruited through a convenience sample. Results: Sexual Health patients are reluctant to get involved in PPI work, often because of embarrassment. PPI work was highly variable with some reliance on customer satisfaction approaches. Patients reported not being asked for feedback and wanted to know what PPI is for. Services cited under-resourcing and a lack of time as barriers to improving PPI work. Discussion: Improving the use of patient's voice in sexual health needs through clarity of purpose (measured against outcomes), better communication with patients, and the exploration of flexible methods that respect patients' needs for anonymity. Next steps will be outlined.